Ebstein’s Anomaly: Epidemiology, Causes and Management Options - Tripathi, Ajay Kumar; Ghosh, Niladry S.; Kumari, Mamta; Dubey, Anubhav; Shukla, Alok Kumar (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
Ebstein's abnormality is an intricate congenital deformity of the tricuspid valve. Newborn and infant health is an often-discussed topic. The condition exhibits a wide range of severity and medical characteristics, necessitating tailored treatment for each patient. This article provides an account of the inherent characteristics and progression of Ebstein's abnormalities in children and adolescents. This includes the indications and manifestations that appear at the time of diagnosis. This section describes the contemporary methods used to categorize Ebstein's abnormalities. We provide diagnostic techniques for assessing the severity of illnesses that have the potential to enhance decision-making in surgical procedures. Furthermore, we explore several surgical alternatives for neonates in severe conditions, as well as many surgical procedures following the operation. In order to effectively enhance both the duration and quality of life for this complex and diverse group of patients, it is essential to possess sufficient information and comprehension of the aforementioned factors. Effective management requires a nuanced and personalized approach. It is crucial to have an accurate understanding of the many anatomical and hemodynamic factors, related abnormalities, and available treatment choices.